Membangun Generasi Berinteraksi Pendidikan Karakter dalam Kurikulum Nasional - Ajwita, Ajwita; Puan Khairani; Cut Kumala Sari (Mutiara Pendidikan dan Olahraga, 2025)
Character education is a fundamental element in Indonesia’s national education system, especially amid the growing challenges of the digital era and globalization. This article explores the urgency of character education as a means of shaping a generation that excels not only academically but also morally and socially. Using a qualitative approach through literature review, the study highlights the importance of integrating character values into the national curriculum, the role of teacher role models, and the collaboration between schools, families, and communities. The findings indicate that consistently implemented, integrative character education can serve as a strategic solution to moral decline and as a foundation for building a civilization rooted in noble values.